Prevalence of Long Hours and Skilled Women's Occupational Choices - Patricia Cortes; Jessica Pan (Institute for the Study of Labor (IZA), 2016)
Gender differences in occupations account for a sizable portion of the persistent gender pay gap. This paper examines the relationship between the demand for long hours of work (as proxied for by the share of men working 50 or more hours per week) and skilled women's occupational choice. Exploiting variation across 215 occupations and four decades in the US, we find that the prevalence of overwork in an occupation significantly lowers the share of college educated young married women with children working in that occupation. These findings are robust to controlling for the occupational distribution of similarly aged males and married women with no children, suggesting that the prevalence of overwork reduces the desirability of the work environment for women with family responsibilities and is not merely proxying for other demand side shocks. Similar results are obtained using a panel of European countries.
Keywords: J16; J24; J22; 330; long hours; overwork; occupational choice; gender